2017
DOI: 10.1097/inf.0000000000001542
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Safety of a Booster Injection of DTap-IPV//Hib (Pentaxim) Administered Concomitantly With Tetravalent Dengue Vaccine in Healthy Toddlers 15–18 Months of Age in Mexico

Abstract: Coadministration of the DTaP-IPV//Hib booster vaccine with CYD-TDV has no observed impact on the immunogenicity or safety profile of the DTaP-IPV//Hib booster vaccine. No difference was observed on the CYD-TDV profile when administered concomitantly or sequentially with the DTaP-IPV//Hib booster vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
4
1
Order By: Relevance
“…The overall incidence of solicited injection-site (15.4%) and systemic (24.6%) reactions in this study was lower than those reported in the randomized clinical trial of the study vaccine in South Korea (solicited injection-site, 75.6%; systemic, 80.9%) [ 7 ], and other studies from South Korea (solicited injection-site, 73.5%; systemic, 69.0%) [ 22 ], booster study from Mexico (solicited reactions, 40.8%) [ 23 ], and a study from Turkey in which the study vaccine was co-administered with hepatitis B vaccine in the comparator arm (solicited injection-site, 38.9%; systemic, 76.30%) [ 24 ]. The incidence of solicited reactions was lower in this study, possibly because the safety was only assessed for one of the three doses of the primary series in this observational study, compared with randomized clinical trial conducted in accordance with Good Clinical Practices, in which all study participants had received three doses of the primary series.…”
Section: Discussioncontrasting
confidence: 56%
“…The overall incidence of solicited injection-site (15.4%) and systemic (24.6%) reactions in this study was lower than those reported in the randomized clinical trial of the study vaccine in South Korea (solicited injection-site, 75.6%; systemic, 80.9%) [ 7 ], and other studies from South Korea (solicited injection-site, 73.5%; systemic, 69.0%) [ 22 ], booster study from Mexico (solicited reactions, 40.8%) [ 23 ], and a study from Turkey in which the study vaccine was co-administered with hepatitis B vaccine in the comparator arm (solicited injection-site, 38.9%; systemic, 76.30%) [ 24 ]. The incidence of solicited reactions was lower in this study, possibly because the safety was only assessed for one of the three doses of the primary series in this observational study, compared with randomized clinical trial conducted in accordance with Good Clinical Practices, in which all study participants had received three doses of the primary series.…”
Section: Discussioncontrasting
confidence: 56%
“…The third study (Philippines) assessed co-administration of a tetanus/diphtheria/ pertussis vaccine in individuals 9 to 60 years (CYD66). 73,[75][76][77] Safety and immunogenicity summary of non-efficacy studies Dengvaxia's® acute safety profile was found to be similar to licensed Yellow fever vaccine (YF-VAX®, Sanofi Pasteur, Swiftwater, PA) and not affected by pre-existing Yellow fever immunity. Most volunteers seroconverted in the monovalent DENV-2 trial (CYD01), and pre-existing Yellow fever immunity contributed to a more cross-reactive and enduring anti-DENV antibody response.…”
Section: Phase 1-3 Trial Reviewmentioning
confidence: 97%
“…Previous studies of the co-administration of CYD-TDV with human papillomavirus vaccines in children 9–14 years of age (NCT02979535 and NCT02993757), or with DTaP inactivated polio vaccine and Haemophilus influenzae type b vaccine in toddlers 15–18 months of age, 22 have demonstrated that CYD-TDV could be administered concomitantly with other vaccines, safely and without affecting immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of the co-administration of CYD-TDV with human papillomavirus vaccines in children 9-14 years of age (NCT02979535 and NCT02993757), or with DTaP inactivated polio vaccine and Haemophilus influenzae type b vaccine in toddlers 15-18 months of age, 22 could be administered concomitantly with other vaccines, safely and without affecting immunogenicity. In participants who were baseline dengue seropositive, the neutralizing antibody responses at 28 days post-first CYD-TDV dose for serotypes 1-4, were consistent with those reported in the previous pivotal trials of CYD-TDV in highly endemic countries.…”
Section: Discussionmentioning
confidence: 99%